Utilization of a high-amylase corn hybrid in beef cattle finishing diets - Baker, Adrian Neal (Kansas State University, 2023)
Four experiments were conducted to evaluate Enogen Corn (EC) for production of corn silage and steam-flaked corn (SFC). In experiment 1, whole corn plant material from EC and a commercial corn hybrid utilized for corn silage (CON) were harvested and ensiled for 30, 60, 90, 120, or 240 d. Ensiled forages were analyzed for dry matter, volatile fatty acids (VFA), lactate, and aerobic stability. Silages produced from EC had greater concentrations of acetate compared to CON silages (144 vs 128 mM, P<0.01) and remained aerobically stable for a longer duration than CON silage (P<0.05). A second experiment was conducted to evaluate the initial 30-d of ensiling EC compared to CON. Freshly chopped corn plant samples were ensiled for 2, 4, 6, 8, 10, 12, 15, 18, 21, 24, 27, or 30 d. After ensiling, samples were analyzed for pH, VFA and lactate concentrations. An effect of forage type was observed, with silage produced from EC having greater lactate concentrations compared to CON (332.0 vs 291.7 mM, P<0.01). Experiment 3 evaluated starch gelatinization and retrogradation characteristics from ground whole corn (EC or CON) at moisture levels of 20, 30, 40, 50, 60, 70, or 80%. There were no grain type by moisture interactions observed for gelatinization temperatures or enthalpy (P>0.10). Retrogradation was affected by the interaction of grain type by moisture content, with EC at 70 and 80% moisture having lower recrystallization of starch compared to EC at lower moisture levels and CON grain at all moisture levels (P<0.05). Experiment 4 compared steam flaking EC versus CON at high-moisture. Deionized water was added at a 50% w/w to whole grains to measure water absorption and tempered to achieve moisture levels greater than commonly utilized in industry. Grains were flaked to a common bulk density and starch solubles were measured. Starch solubles were greater for steam-flaked EC compared to CON (4.7 vs 2.3 %, respectively; P<0.05). Three experiments were conducted to evaluate the performance and/or digestibility of EC as corn silage, SFC, and a combination dry-rolled corn (DRC)/ high-moisture corn (HMC). Experiment 5 was conducted to evaluate performance, carcass characteristics, and meat quality of steers fed EC or CON as corn silage and/or SFC in a 2 x 2 factorial treatment arrangement. Steers (n=960; 388± 7.4 kg) were fed finishing diets for 138, 152, or 166 d. Steers fed EC silage and CON grain had greater hot carcass weights compared to other treatments (P<0.05) and longissimus lumborum steaks from steers consuming EC grain were observed to contain greater poly-unsaturated fat content compared to steaks from the CON grain treatment (P<0.05). Two experiments were conducted to compare digestibility of EC versus CON utilizing different grain processing methods. Experiment 6 utilized cannulated steers (n=7) fed finishing diets comprised the DRC/HMC combinations as either EC or CON in a replicated cross over design. Digesta samples were collected at h 0, 8, and 16 on d 11 through 14, advancing 2-h each day to represent a 24-h post-feeding cycle. Grain type did not affect total-tract digestion (P>0.10), but small intestinal nitrogen digestion tended to be greater with steers fed EC grain combination compared to CON grain (69.8 vs 59.5; P=0.09). Experiment 7 utilized the same cannulated steers in a similar study design as previously described; however, fed finishing diets containing SFC produced from either EC or CON grain flaked to 390 g/L and 360 g/L, respectively. Grain type did not affect intestinal or total-tract starch digestion (P>0.10). Ruminal fluid of steers fed steam-flaked EC were observed with greater butyrate content compared to steers fed steam-flaked CON grain (23.3 vs 18.7 mM, respectively; P<0.01). Ensiling EC modifies VFA, and lactate produced and improves aerobic stability of the silage produced from that forage type. Furthermore, gelatinized EC grain may be less susceptible to retrogradation due to amylolytic activity on the starch. Enogen corn fed as corn silage improves performance and meat produced from cattle consuming EC as grain have greater poly-unsaturated lipid content compared to cattle fed CON grains. Enogen corn fed as SFC or a combination of DRC/HMC does not affect site and extent of starch digestion; however, EC flaked to at a greater flake density compared to conventional corn had similar digestibility of starch. Enogen corn fed as a combination of DRC/HMC tended to improve small intestinal nitrogen digestion compared to conventional corn.
Keywords: Amylase